Razvoj enačbe za oceno časa zakasnitve za slovenska porečja - Mavri, Deja (Gradbeni vestnik, 2023)
Information on design discharge values and design hydrographs is crucial for the design of hydro-engineering structures and structural and non-structural flood control measures. These variables can also be determined using a rainfall-runoff hydrological model. If there are insufficient data to calibrate the hydrological model, the model parameters must be estimated according to the characteristics of the catchment. One of the parameters that is also considered by the commonly used hydrological model HEC-HMS is the catchment lag time. So far, empirical equations developed in other geographic areas (e.g., USA) have been used to estimate this parameter in Slovenian engineering practice. This article shows the methodology applied for developing the empirical equation for estimating the lag time parameter based on measured precipitation and discharge data using 20 selected river catchments in Slovenia. The derived equation can thus be used to estimate the lag time parameter in the case of ungauged catchments. Further studies need to be conducted in order to evaluate the performance of the proposed equations.
Keywords: catchment; čas zakasnitve; empirical equation; empirična enačba; hidrološko modeliranje; hydrological modelling; lag time; odtok; padavine; porečje; rainfall; runoff